1999
DOI: 10.1055/s-2007-971146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recovery Duration on Muscular Power and Blood Lactate During the Bench Press Exercise

Abstract: In order to assess the effect of recovery on power and blood lactate, 10 males performed 10 sets (S1 to S10) of 6 repetitions of bench press at 70% of their maximal strength, with 1 (Prot1), 3 (Prot3) or 5 (Prot5) min rest between sets. From the measurements of force and displacement of the bar, mean power during each repetition (MPR) and set (MPS), were calculated. Blood lactate was evaluated before and immediately after each set. No significant variations in power or blood lactate occurred during prot3 and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 12 publications
7
43
1
8
Order By: Relevance
“…For example, Abdessemed et al (1999) observed no significant reduction in mean power, during 10 sets of heavy resistance exercise, when 180 or 300 seconds inter-set rest was prescribed. However, significant decreases in power were observed, both between and within sets, when the rest interval was reduced to 60 seconds.…”
Section: Inter-set Rest Periods -Power Testingmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, Abdessemed et al (1999) observed no significant reduction in mean power, during 10 sets of heavy resistance exercise, when 180 or 300 seconds inter-set rest was prescribed. However, significant decreases in power were observed, both between and within sets, when the rest interval was reduced to 60 seconds.…”
Section: Inter-set Rest Periods -Power Testingmentioning
confidence: 93%
“…However, significant decreases in power were observed, both between and within sets, when the rest interval was reduced to 60 seconds. Abdessemed et al (1999) therefore argued that the length of the inter-set rest periods had a significant influence on subsequent muscle performance, and that 180 seconds rest appears sufficient to maintain constant power outputs during exercise with multiple repetitions. While these findings suggest that short rest periods (e.g.…”
Section: Inter-set Rest Periods -Power Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…O mesmo não ocorre quando os intervalos são curtos ou inexistentes. Assim, a velocidade de movimento e a potência muscular caem rapidamente 3,26 , dependendo do nível de treinamento do atleta 4,34,37,[89][90][91] . Em princípio, há dois aspectos que vão condicionar o surgimento da fadiga: o nível de treinamento e as características musculares.…”
Section: Comportamento Mecânico Durante O Trabalho De Repetição Da Forçaunclassified
“…Por outro lado, possuem menor capacidade de manter a produção de força durante longos períodos 80 . Assim, a seleção do período adequado de descanso entre séries é fundamental para a manutenção da velocidade de execução, da taxa de produção de força e potência máxima durante o treinamento 11,34,83,[91][92][93][94][95] .…”
Section: Comportamento Mecânico Durante O Trabalho De Repetição Da Forçaunclassified